2016
DOI: 10.4103/0301-5742.198607
|View full text |Cite
|
Sign up to set email alerts
|

The current evidence and implications of lingual orthodontics

Abstract: The growing interest in lingual orthodontics is perhaps a reflection of the social and esthetic issues of orthodontics being addressed as more adults seek treatment. The issue remains confounded by the clinical manipulation of the appliance, the patient comfort, and the predictability of outcomes. For any technique or system to succeed, it must address the above three issues directly.The evidence available on lingual orthodontics traces a very clear and predictable pattern. The 80's were devoted to the limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(39 reference statements)
0
4
0
5
Order By: Relevance
“…Several studies have noted that the advancement in lingual systems have reduced limitations and allowed clinicians to successfully treat any case they would treat with traditional labial systems to a satisfactory level, including those combined with Herbst appliance and orthognathic correction of skeletal discrepancies ( 5 , 6 ). Yet, our study showed that more than half of the lingual practitioners are hesitant to treat complex cases with lingual braces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have noted that the advancement in lingual systems have reduced limitations and allowed clinicians to successfully treat any case they would treat with traditional labial systems to a satisfactory level, including those combined with Herbst appliance and orthognathic correction of skeletal discrepancies ( 5 , 6 ). Yet, our study showed that more than half of the lingual practitioners are hesitant to treat complex cases with lingual braces.…”
Section: Discussionmentioning
confidence: 99%
“…Many esthetic appliances like lingual braces, ceramic brackets, clear aligners and coated esthetic archwires are currently available with their own advantages and disadvantages. However, lingual braces currently provide the ultimate esthetic advantages of being inconspicuous and capable of performing orthodontic tooth movements similar to traditional labial brackets ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…La técnica de unión indirecta es la clave para el éxito de la ortodoncia lingual ya sea esta empleada de forma manual utilizando los modelos dentales de los pacientes o mediante la utilización de la técnica digital o personalizada. Cualquiera que se elija no influirá en el resultado del tratamiento siempre y cuando el cementado de los brackets sea de forma precisa y en la posición deseada (Saini et al, 2016).…”
Section: Biomecánica En Ortodoncia Lingualunclassified
“…Al analizar la ortodoncia lingual en los tres planos del espacio, se puede observar que en el plano sagital aplicando una fuerza de intrusión igual que sea igual a la fuerza de retracción, el vector de fuerza neta dará como resultado una fuerza de inclinación lingual, por lo que se debe realizar movimientos ligeros para generar una retracción en masa. En el plano vertical lo ideal es primero corregir las inclinaciones y luego realizar los movimientos de intrusión y finalmente, en el plano horizontal el momento de rotación va a ser menor en el lado lingual que en el labial, sin embargo, es importante destacar que el manejo clínico en casos de apiñamiento es más complicado motivo por el cual en esos casos se requiere de alambres más elásticos que ayuden en los movimientos que se necesita emplear (Rathod et al, 2020;Saini et al, 2016).…”
Section: Biomecánica En Ortodoncia Lingualunclassified
See 1 more Smart Citation